Using the Kirkpatrick Model to evaluate the Maternity and Neonatal Emergencies (MANE) programme: Background and study protocol. Issue 1 (2nd February 2020) - Cullinane, Meabh; McLachlan, Helen L; Newton, Michelle S; Zugna, Stefanie A; Forster, Della A
Abstract : Introduction: Over 310 000 women gave birth in Australia in 2016, with approximately 80 000 births in the state of Victoria. While most of these births occur in metropolitan Melbourne and other large regional centres, a significant proportion of Victorian women birth in local rural health services. The Victorian state government recently mandated the provision of a maternal and neonatal emergency training programme, called Maternal and Newborn Emergencies (MANE), to rural and regional maternity service providers across the state. MANE aims to educate maternity and newborn care clinicians about recognising and responding to clinical deterioration in an effort to improve clinical outcomes. This paper describes the protocol for an evaluation of the MANE programme. Methods and analysis: This study will evaluate the effectiveness of MANE in relation to: clinician confidence, skills and knowledge; changes in teamwork and collaboration; and consumer experience and satisfaction, and will explore and describe any governance changes within the organisations after MANE implementation. The Kirkpatrick Evaluation Model will provide a framework for the evaluation. The participants of MANE, 27 rural and regional Victorian health services ranging in size from approximately 20 to 1000 births per year, will be invited to participate. Baseline data will be collected from maternity service staff and consumers at each health service before MANE delivery, and at four time-points post-MANE delivery. There will be four components to data collection: a survey of maternity services staff; follow-up interviews with Maternity Managers at health services 4 months after MANE delivery; consumer feedback from all health services collected through the Victorian Healthcare Experience Survey; case studies with five regional or rural health service providers. Ethics and dissemination: This evaluation has been approved by the La Trobe University Science, Health and Engineering College Human Ethics Sub-Committee. Findings will be presented to project stakeholders in a deidentified report, and disseminated through peer-reviewed publications and conference presentations.